Unhealthy food and beverage marketing to children on digital platforms in Aotearoa, New Zealand - Kelly Garton; Sarah Gerritsen; Fiona Sing; Karen Lin; Sally Mackay (BMC, 2022)
Abstract Background Children's exposure to unhealthy food and beverage marketing has a direct impact on their dietary preference for, and consumption of, unhealthy food and drinks. Most children spend time online, yet marketing restrictions for this medium have had slow uptake globally. A voluntary Children's and Young People's Advertising (CYPA) Code was implemented in Aotearoa, New Zealand (NZ) in 2017. This study explores the Code's limitations in protecting children from harmful food and beverage marketing practices on digital platforms accessible to children. Methods A cross-sectional content analysis of company websites (n = 64), Facebook pages (n = 32), and YouTube channels (n = 15) of the most popular food and beverage brands was conducted between 2019 and 2021 in NZ. Brands were selected based on market share, web traffic analysis and consumer engagement (Facebook page 'Likes' and YouTube page views). Analysis focused on volume and type of food posts/videos, level of consumer interaction, nutritional quality of foods pictured (based on two different nutrient profile models), and use of specific persuasive marketing techniques. Results Eighty-one percent of websites (n = 52) featured marketing of unhealthy food and beverages. Thirty-five percent of websites featuring unhealthy food and beverages used promotional strategies positioning their products as 'for kids'; a further 13% used 'family-oriented' messaging. Several websites featuring unhealthy products also had designated sections for children, 'advergaming,' or direct messaging to children. Eighty-five percent of all food and drink company Facebook posts and YouTube videos were classified as unhealthy. Twenty-eight percent of Facebook posts for unhealthy products featured persuasive promotional strategies, and 39% premium offers. Nearly 30% of YouTube videos for unhealthy food and beverages featured promotional strategies, and 13% premium offers. Ten percent of Facebook posts and 13% of YouTube videos of unhealthy food and beverages used marketing techniques specifically targeting children and young people. Conclusions The voluntary CYPA Code has been in effect since 2017, but the inherent limitations and loopholes in the Code mean companies continue to market unhealthy food and beverages in ways that appeal to children even if they have committed to the Code. Comprehensive and mandatory regulation would help protect children from exposure to harmful marketing.